Methodological and procedural errors related to academic research questions and ways to correct them - Difel , Samiha (The Algerian Historical Journal, 2026)
Each of us has his own way of reaching the goal he seeks to achieve, but science has a special way of achieving the goal, and this method has always been overlooked by many researchers and students, which makes it difficult for them to reach good results in their research. Therefore, we seek, through this presented research paper, to highlight the technical methodological and procedural errors in this dissertation. Especially the errors related to the questions asked, and the way they are presented, and we will try to provide some solutions that have proven successful during our course in training doctoral and master’s students in order to bring them to safety in their research.